Prognostic factors for unresectable hepatocellular carcinoma treated with transcatheter arterial chemoembolisation combined with radiotherapy - Qi, Zhonghua; Zhao, Qianqian; Wang, Renben (Translational Cancer Research, 2018)
Background: To assess the prognostic factors for unresectable hepatocellular carcinoma (uHCC) treated with transcatheter arterial chemoembolisation (TACE) combined with radiotherapy (RT). Methods: All 101 patients who had received TACE combined with RT from January 2010 to December 2015 were included in this retrospective study. Tumor response and overall survival rate was analysed for all patients. Univariate and multivariate analyses were used to determine prognostic factors. Results: The objective response rate was achieved for 73.3% of patients. The median survival time was 23 months (range: 3–60 months), and the overall survival rate at 1, 3, 5 years was 80.2%, 26.7% and 7.9%, respectively. Multivariate analysis showed that TNM stage, Child-Pugh classification, TACE times and the total liver volume receiving >20 Gy (V20) were independent prognostic factors for overall survival. Conclusions: The TNM stage, Child-Pugh classification, TACE times and V20 were independent prognostic factors for uHCC patients treated with TACE combined with RT.